MITF Is Mutated in Type 1 Waardenburg Syndrome With Unusual Phenotype. Issue 10 (December 2020) - Li, Wu; Feng, Yong; Chen, Hongsheng; He, Chufeng; Mei, Lingyun; Liu, Xue Zhong; Men, Meichao
Abstract : Background: Waardenburg syndrome (WS) is a rare disorder characterized by varying combinations of sensorineural hearing loss and abnormal pigmentation of the hair and skin. WS is classified into four subtypes (WS1–WS4) based on additional symptoms. Dystopia canthorum is a hallmark of WS type 1. There are two genes linked to WS type 1, including PAX3 and EDNRB. Objective: This study aimed to investigate the genetic etiology of WS type 1 in a pair of twins from China with profound hearing loss, blond hair and eyebrows, dystopia canthorum, and brown irides. Methods: The target capture sequencing and Whole-exome sequencing were performed to detect mutations in WS-related genes. Results: A novel de novo frameshift mutation, p.L341Rfs*18 in MITF was identified in the twins. Hearing thresholds showed substantial improvements following cochlear implantation with a pure-tone average of 30 dB in free-field conditions. Conclusions: The study showed the new genotype–phenotype correlations of MITF to WS type 1. Further molecular analysis is necessary to reappraise the current classification on WS. Abstract : Supplemental Digital Content is available in the text